Predicting survival with the Heidelberg prognostic model after salvage radiosurgery of previously irradiated progressive high-grade gliomas - Ampil, Federico L.; Richards, Troy; de la Cruz, Nestor; Caldito, Gloria (Therapeutic Radiology and Oncology, 2019)
The study aimed to determine which patients with previously irradiated progressive high-grade gliomas (PHGG) are likely to benefit from salvage stereotactic radiosurgery (SSRS) using the Heidelberg prognostication model (HPM). Twenty-five study participants with PHGG underwent SSRS between 2000 and 2010. There were 5 and 20 patients with determined low or high HPM prognostic scores, respectively. Overall median survival (MS) was 7 months (range, 1 to 32 months). The 6-, 12- and 24-month crude survival rates (CSR) were 60%, 28% and 16%, respectively. The MS and CSRs for the low-scoring patients were 20 months, 100%, 100% and 20%, respectively; for the 20 individuals with higher scores, the corresponding findings were 8 months, 75%, 35% and 10%, respectively. Among the evaluable 11 patients, the quality of remaining life after therapy was acceptable in approximately half of the cases. Acute and late toxicity were not observed in the retreated subjects. A trend towards improved survival, even if not statistically significant, was observed in the low HPM scoring patients. More documentation of favorable effects from the application of SSRS in people with PHGG is required to support its useful role as a second line treatment.